Surface Functionalization of Iron Oxide Nanoparticles with Gallic Acid as Potential Antioxidant and Antimicrobial Agents - Shah, S.T.; Yehya, W.A.; Saad, O.; Simarani, K.; Chowdhury, Z.Z.; Alhadi, A.A.; Al-Ani, L.A. (MDPI, 2017)
In this research, we report the size‐controlled synthesis and surface‐functionalization of magnetite with the natural antioxidant gallic acid (GA) as a ligand, using in situ and post‐synthesis methods. GA functionalization provided narrow size distribution, with an average particle size of 5 and 8 nm for in situ synthesis of gallic acid functionalized magnetite IONP@GA1 and IONP@GA2, respectively, which are ultra‐small particles as compared to unfunctionalized magnetite (IONP) and post functionalized magnetite IONP@GA3 with average size of 10 and 11 nm respectively. All the IONPs@GA samples were found hydrophilic with stable aggregation state. Prior to commencement of experimental lab work, PASS software was used to predict the biological activities of GA and it is found that experimental antioxidant activity using 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay and antimicrobial studies using well diffusion method are in good agreement with the simulated results. Furthermore, the half maximal inhibitory concentration (IC50) values of DPPH antioxidant assay revealed a 2–4 fold decrease as compared to unfunctionalized IONP. In addition to antioxidant activity, all the three IONP@GA proved outstanding antimicrobial activity while testing on different bacterial and fungal strains. The results collectively indicate the successful fabrication of novel antioxidant, antimicrobial IONP@GA composite, which are magnetically separable, efficient, and low cost, with potential applications in polymers, cosmetics, and biomedical and food industries.